Time-resolved fourier transform infrared emission spectroscopy of NH radical in the X3Σ− ground state. (November 2022) - Pastorek, Adam; Clark, Victoria H.J.; Yurchenko, Sergei N.; Civiš, Svatopluk
Highlights: T-R FTIR spectroscopy of NH radical. Generation of species in glow discharge of N2 +H2 and N2 +NH3 +Ar mixtures. Analysis of decomposition products together with time profiles. Pure rotation transitions first observed in the lab by use of cold source. Non-LTE modelling of obtained spectra. Abstract: The NH radical is an extremely important specie in nitrogen chemical reaction networks, in the interstellar medium and atmospheric chemistry. Time resolved Fourier transform spectroscopy technique in the frequency range 10–13 µm has been applied for the measurement of a pure rotational spectrum of the NH free radical (NH) in the ground X 3 Σ − electronic state. Twelve high N (26–29) triplet-resolved pure rotation lines of NH were experimentally observed in the laboratory and compared with satellite ACE (Atmospheric Chemistry Experiment) solar data. In addition, discharge-generated vibration-rotation NH radical bands in the spectral range 1923–3571 cm −1 have been measured with a microsecond time resolution and spectral resolution of 0.02 cm −1 . The spectra of the NH radical have been studied in two experimental arrangements. Firstly, in a pulsed positive column discharge of pure hydrogen-nitrogen mixture and secondly, in a discharge of nitrogen-ammonia mixture in the presence of argon buffer gas. Both production methods are described and compared. The population analysis of the experimental spectra was performed via modelling using the accurate MoLLIST line lists for NH. It was shown that laboratory data can be well reproduced by use of a mixture of the local-thermal-equilibrium (LTE) and non-LTE models corresponding to high temperatures (up to 8000 K and up to 6000 K rotational).